2018
DOI: 10.3233/bmr-169615
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of manual therapy and exercise for treating non-specific neck pain: A systematic review

Abstract: OBJECTIVE: To review and update the evidence for different forms of manual therapy (MT) and exercise for patients with different stages of non-specific neck pain (NP). Data sources: MEDLINE, Cochrane-Register-of-Controlled-Trials, PEDro, EMBASE.METHOD: A qualitative systematic review covering a period from January 2000 to December 2015 was conducted according to updated-guidelines. Specific inclusion criteria only on RCTs were used; including differentiation according to stages of NP (acute – subacute [ASNP] o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 95 publications
7
98
0
3
Order By: Relevance
“…To our knowledge, this is the rst study that describes physiotherapeutic intervention for neck pain associated with block vertebra. Literature supports the ndings of our case report and suggests that exercise alone or combined with manual therapy does result in signi cant pain reduction [7], [8]. The authors used a speci c patient-reported issue as an outcome measure, the sitting duration showed improvement.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the rst study that describes physiotherapeutic intervention for neck pain associated with block vertebra. Literature supports the ndings of our case report and suggests that exercise alone or combined with manual therapy does result in signi cant pain reduction [7], [8]. The authors used a speci c patient-reported issue as an outcome measure, the sitting duration showed improvement.…”
Section: Discussionsupporting
confidence: 83%
“…There is currently a lack of strong evidence to support most conservative interventions for the management of CNSNP (Hidalgo et al, ), including those involving CBA. In response to this assertion, investigators have recommended that future studies be designed such that the baseline or comparison intervention is similar across subjects (Hidalgo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for our findings of no clinically meaningful difference in function or pain outcomes when comparing intervention with GA/GEX versus no GA/GEX is that the patient education elements of the McKenzie approach may be similar to those of GA/GEX, thereby negating much of the effect of GA/GEX in our study population. One study examining patients with neck pain (Kjellman & Oberg, 2002) found a significant reduction in distress related depressive symptoms There is currently a lack of strong evidence to support most conservative interventions for the management of CNSNP (Hidalgo et al, 2017), including those involving CBA. In response to this assertion, investigators have recommended that future studies be designed such that the baseline or comparison intervention is similar across subjects (Hidalgo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some systematic reviews showed a moderate level of evidence for the clinical efficacy of manual therapy, massage, and spinal manipulations in patients with low back pain [25][26][27]. Tuina, one of the key noninvasive therapies of traditional Chinese medicine, is a Chinese manual manipulation.…”
Section: Introductionmentioning
confidence: 99%